Thulium laser enucleation of the prostate plus thulium fiber laser therapy for benign prostatic hyperplasia combined with bladder stones - Chen Wang; Yuanwei Li; Yongjun Yang; Junjie Chen; Zhuo Li; Guangqing Song; Jia Chen; Liu Zhe; Yili Teng; Qiang Lu (Videosurgery and Other Miniinvasive Techniques)
Introduction: Population aging is associated with increased incidence of benign prostatic hyperplasia (BPH), which may be complicated by bladder stones (BSs). The conditions are successfully treated with transurethral enucleation of the prostate (TUEP) plus bladder lithotomy. However, open surgery is associated with higher blood loss, larger incisions, prolonged operative time, and may impede patient recovery.